2013
DOI: 10.1080/2150704x.2013.823673
|View full text |Cite
|
Sign up to set email alerts
|

DInSAR estimation of land motion using intermittent coherence with application to the South Derbyshire and Leicestershire coalfields

Abstract: Differential interferometric synthetic aperture radar (DInSAR) is a recognized remote sensing method for measuring the land motion occurring between two satellite radar acquisitions. Advanced DInSAR techniques such as persistent scatterers (PS) and small baseline methods are excellent over urban and rocky environments but generally poor over more rural and natural terrain where the signal can be intermittently good and bad. Here, we describe the ISBAS (Intermittent Small Baseline Subset) method, which appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
143
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 5 publications
1
143
0
1
Order By: Relevance
“…Previous studies have shown similar types of motions within former coal mining areas in the UK, for instance in Stoke-on-Trent [11] [17] , Durham and Northumberland [1], and the South Derbyshire and Leicestershire Coalfields [30]), as well as overseas, for instance in south Limburg (The Netherlands) and across Germany and Belgium [9], with observed annual rates of ground uplift as high as a few centimetres per year. This paper will present the first ISBAS results for South Wales and compare them to standard SBAS results.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…Previous studies have shown similar types of motions within former coal mining areas in the UK, for instance in Stoke-on-Trent [11] [17] , Durham and Northumberland [1], and the South Derbyshire and Leicestershire Coalfields [30]), as well as overseas, for instance in south Limburg (The Netherlands) and across Germany and Belgium [9], with observed annual rates of ground uplift as high as a few centimetres per year. This paper will present the first ISBAS results for South Wales and compare them to standard SBAS results.…”
Section: Introductionmentioning
confidence: 97%
“…For the implementation of the ISBAS approach this value was used as a threshold to select coherent pixels within each interferogram, so that for each image pixel, only those interferograms showing coherence higher than 0.25 were kept for the subsequent processing steps, provided that the number of coherent layers for those pixels exceeded 50, which was used as threshold for the selection of intermittently coherent targets (see also [30]). This threshold allows a trade-off between uncertainty in the ISBAS solutions and spatial coverage of results to be adopted.…”
Section: Isbas Processing Implementationmentioning
confidence: 99%
See 2 more Smart Citations
“…We offer a wide selection of references below [2][3][4][5][6][7][8], each of which clearly identifies the ISBAS acronym as Intermittent SBAS. The first peer-reviewed journal [2] in this instance was in 2013 and so the use of the acronym certainly predates the Vajedian et al reference by at least two years.…”
mentioning
confidence: 99%